Study of hot corrosion of single crystal superalloys and platinum-aluminide coatings - Encinas-Oropesa, Adriana (Cranfield University, 2005)
At the present time, combined cycle systems for power generation (e. g. IGCC), offer increased efficiency of power generation and lower environmental emissions, specifically C02, SOxg, and NO,,, as well as being adaptable to most fossil fuels. Economic factors, such as the cost of the materials must be considered. Materials influence the service lifetime in the required operational environment. Solid fuels like coal and biomass produce different combustion environments containing a range of contaminants that, when they reach their melting points, may cause accelerated corrosion, affecting directly the service life time of the gas turbine constructional materials. This accelerated corrosion is known as Hot Corrosion. The aim of this study was to develop, an understanding of the influence of these environmental factors on rate of hot corrosion of modem turbine materials, i. e. the single crystal alloys CMSX4 the SC2 , both uncoated and PtAl coated that are needed for a gas turbine blade and vanes operating in a range of hot corrosion environments expected in an lGCC plant. To achieve this aim, a series of laboratory corrosion tests was planned to simulate the same corrosion environment as in industrial high temperature gas turbine operation. Following established procedures for corrosion testing, samples were exposed in a controlled atmosphere furnace to a mix of gases (air/SO241CI) with a cyclic exposure time of 50 and/or 100h duration. Each cycle, samples were removed to be recoated with an alkali salt mixture to a total exposure time of 500h and or 1000h. Cross sections were examined by SEM/EDX to identify the mode of hot corrosion attack. To quantify the rate of corrosion, samples were measured pre-exposure and post-exposure, and this corrosion data was statistically assessed. Finally, from this quantitative data, life prediction models were developed to describe/predict the onset of hot corrosion and the corrosion rates observed under different gas compositions, and various deposition fluxes, both at typical type I and type II hot corrosion temperatures in terms of incubation and propagation periods. Separate models have been developed for the two single crystals superalloys: CMSX4 and SC2, in both the uncoated and platinum aluminide coated condition. The goodness of fit as defined by the regression coefficient varies from 0.88 to 0.99 for the propagation models at 700 and 900'C. The incubation models are as precise at 7001C but less precise at 9001C with regression coefficients of 0.78-0.94. I